A lignin-based controlled/sustained release hydrogel by integrating mechanical strengthening and bioactivities of lignin - Bowei Wang; Dingkun Qiu; Yihui Gu; Zhu Shan; Ruonan Shi; Jing Luo; Shuang Qi; Yilin Wang; Bo Jiang; Yongcan Jin (Journal of Bioresources and Bioproducts)
The favorable antioxidant and antimicrobial activities of lignin have been shown to promote wound healing. However, the accumulation of lignin in high concentrations in the body brings about varying degrees of biotoxicity. Herein, a controlled/sustained release polyvinyl alcohol/chitosan/sulfonated lignin hydrogel (PVA-CS-L) integrated mechanical strengthening and bioactivities of lignin was developed. The lignin-induced non-covalent bond network (van der Waals force, hydrogen and electrostatic interactions) promoted energy dissipation when the hydrogel was subjected to stretching and compression. This endowed the PVA-CS-L hydrogel with improved tensile (∼36 kPa) and compressive strength (∼900 kPa), as well as compressive toughness (∼9.0 MJ/m3), which were superior to the polyvinyl alcohol/chitosan hydrogel (PVA-CS) (31 kPa, 680 kPa, and 7.5 MJ/m3, respectively). The construction of electrostatic interaction could not only slow down the sudden release of lignin but also make the hydrogel exhibit a good pH-sensitive behavior of controlled-release lignin. Also, the developed hydrogel had good biocompatibility and the released lignin had reactive oxygen species scavenging as well as inhibitory activity against Staphylococcus aureus. Finally, preliminary evaluation of drug delivery reveals that the presence of lignin enabled the hydrogel to exhibit longer-lasting controlled/sustained epigallocatechin gallate release properties. Such lignin-based controlled/sustained release hydrogel that integrates the molecular structure and biological difunctional features of lignin gives new insight into cost-effective, easy-to-operate manufacturing of load-bearing and bioactive materials.